Analysis Of Mechanical Properties Of Concrete SCC High Quality With The Use Of Technology High Volume Fly Ash Concrete - Mulyanto, Tri, Mochamad Solikin, S.T., M.T., Ph.D, Budi Setiawan, S.T., M.T (2015)
The use of concrete as a building material of construction is very commonly used both for residential structures, buildings, roads, bridges and other infrastructure. The use of vibrators for compacting structure with dense reinforcement can not guarantee produce good concrete. Concrete SCC (self compacting concrete) is one of the alternatives to overcome the problem of heavy harness itself to be able to flow to fill the room without any compaction process. The addition of 50% fly ash as a cement substitute material can improve the mechanical properties of concrete. With that tends to form spherical granules and tiny fly ash in addition to functioning as a filler (filler) also have a pozzolan properties that can be applied to the PPC. This study aims to determine the mechanical properties of SCC concrete which include compressive strength, flexural strength, modulus of elasticity and water absorption of concrete. Compressive strength testing is done at the age of 14,28 and 56 days with 4 specimen in each age testing. While testing the flexural strength (3 specimen), modulus of elasticity (2 specimen) and water absorption of concrete (3 specimen) is performed at the age of 56 days. Before testing the test piece be treated by soaking in the soaking tub for a day prior to the tests / test specimens are dry. Based on test results obtained greatest compressive strength value at each testing age was 40.89 MPa at 14 days, 49.89 MPa at 28 days and 59.56 MPa at the age of 56 days. The flexural strength 6.60 MPa, elasticity modulus 56 588 MPa and water absorption of 1.85%. From the test results show that the compressive strength of concrete strength with the addition of 50% use of fly ash as cement substitutes can improve the strength of concrete from 14 days to 56 days. Keywords: Concrete SCC, the mechanical properties of concrete HVFA